Upaya Hukum dalam Perlindungan Hak Nafkah Anak Akibat Perceraian Orang Tua - Putri, Sophie Hanna; Mairul, Mairul (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to identify the legal measures implemented to safeguard children's maintenance rights in the context of divorce. According to Law Number 16 of 2019, which amends Law Number 1 of 1974 about marriage, it stipulates that following the dissolution of a marriage, the husband remains obligated to give financial support for his children. What legal remedies are available to a child if a father fails to fulfill his support obligations? By addressing the question of the legal remedies available to a kid for the father's failure to fulfill support commitments. The employed research approach is normative jurisprudence, utilizing literature review and analysis of pertinent laws and regulations for data collecting. The research findings indicate that legal actions regarding children's maintenance rights may be initiated in religious courts to safeguard these rights on behalf of mothers. The research concludes that the responsibility for child support rests with the father, as the head of the family, while the woman may assist him. The enforcement of legal safeguards for child support in the context of divorce involves a legal action to ascertain the fulfillment of child support entitlements.